Cosmopolitan regard political membership and global justice - Vernon, Richard (Cambridge Univ. Press, 2010)
"Cosmopolitan theory suggests that we should shift our moral attention from the local to the global. Richard Vernon argues, however, that if we adopt cosmopolitan beliefs about justice we must re-examine our beliefs about political obligation. Far from undermining the demands of citizenship, cosmopolitanism implies more demanding political obligations than theories of the state have traditionally recognized. Using examples including humanitarian intervention, international criminal law, and international political economy, Vernon suggests we have a responsibility not to enhance risks facing other societies and to assist them when their own risk-taking has failed. The central arguments in Cosmopolitan Regard are that what we owe to other societies rests on the same basis as what we owe to our own, and that a theory of cosmopolitanism must connect the responsibilities of citizens beyond their own borders with their obligations to one another"--Provided by publisher.
Keywords: Cosmopolitanism; Political obligation; Politische Ethik; Politische Verantwortung; Weltbürgertum; Gerechtigkeit